BCG lymphadenitis of a healthy infant - Mohamed, Nurul Azmawati; Zaini, Adilahtul Bushro; Rahman, M M (Bangladesh Journal of Medical Science, 2016)
This is a case of a 2-month-old infant who had suppurative lymphadenitis at left axilla after Bacille Calmette Guérin (BCG) vaccination. She presented with a non-healing BCG wound and left axillary swelling associated with one-week fever at 2 months of age. Aspiration under general anaesthesia was done and pus sent for mycobacterium culture grew Mycobacterium tuberculosis complex. The patient improved without anti-tuberculosis treatment. Bangladesh Journal of Medical Science Vol.15(2) 2016 p.283-285